Service Experience and Customer Loyalty to Telecommunication Networks: Evidence from Akwa Ibom State, Nigeria - Ini Smart Udoh; Nfawa Erasmus Usani; Mfon Isaac Effiong (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
The main aim of this study was to investigate the influence of service experience on customer loyalty to telecommunication networks in Uyo, Akwa Ibom State. Fair tariff plans and quality network service were considered indicators of service experience and measured against customer loyalty. The study was anchored on the expectancy confirmatory theory. The quantitative research design approach was employed. The population for the study was voice subscribers from the four telecommunication service providers in the state. The sample size of 400 respondents was determined using the Taro Yamane formula. Respondents were selected using the simple random sampling technique, and data were collected with the use of a 5-point Likert scale questionnaire. The collected data were then analysed using a simple linear regression at the 0.05 level of significance. Findings revealed that both fair tariff plans and quality of network service had a significant influence on customer loyalty. It was therefore concluded that a fair tariff plan and quality network service were significant predictors of customer loyalty to telecommunication providers. Based on the findings, it was further recommended, among others, that telecommunication service providers should ensure that their prices charged on their tariff plans are fair with transparent pricing.